Applying Hamka’s Psychopspiritual Therapy Among University’s Students: Case of Universitas Darussalam Gontor - M. Shohibul Mujtaba; Imroatul Istiqomah; Fitri Setyo Rini (Universitas Muhammadiyah Malang, 2025)
This study addresses the need to evaluate the effectiveness of Hamka’s psychospiritual therapy model in determining the steps, content, methods, strategies, and media applied in its use. For the counseling body at Universitas Darussalam Gontor (UNIDA), assessing this model’s effectiveness serves as a benchmark for the therapy practices already in place. Hamka’s psychospiritual therapy is highly relevant as it offers a therapy approach grounded in Islamic values, holistically integrating psychological and spiritual dimensions in addressing mental health issues. This is a distinct advantage, merging the intellectual legacy of the pesantren tradition with principles of both Islamic and modern psychology. The research aims to measure the effectiveness of Hamka’s therapy model, developed in previous studies, in tackling psychological and mental health issues at UNIDA Gontor, an Islamic boarding school university in East Java with a 24-hour on-campus student program. Employing a quasi-experimental method with an untreated control group design with dependent pre-test and post-test samples, the study divides subjects into control and experimental groups. Results indicate that the therapy model significantly enhances students' psychological well-being, suggesting that Hamka’s model is an effective and holistic approach for mental health issues in Islamic educational settings. The findings underscore its positive impact on counseling practices at UNIDA, supporting its potential broader application in similar environments.